Transformasi Digital Dan Dampaknya Terhadap Kinerja Organisasi Sektor Publik Di Indonesia - Khalik Arifin Harefa; Dermawan Zebua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Digital transformation is one of the main agendas of bureaucratic reform in the Indonesian public sector. The use of information and communication technology is expected to improve efficiency, transparency, and the quality of public services. However, the implementation of digital transformation still faces various challenges, both in terms of human resources, infrastructure, and organizational culture. This study aims to analyze the impact of digital transformation on the performance of public sector organizations based on a review of scientific literature. The research method used is a literature review by examining various national and international journals relevant to the topic of digital transformation and public organization performance. The results of the analysis indicate that digital transformation has a positive influence on improving the performance of public sector organizations, especially in terms of service effectiveness, accountability, and decision-making. However, the success of digital transformation is highly dependent on organizational readiness, apparatus competence, and ongoing policy support. This study is expected to serve as a reference for the government and researchers in developing more effective digital transformation strategies in the public sector.